2018
DOI: 10.1101/451682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Thermodynamic Limit on the Role of Self-Propulsion in Enhanced Enzyme Diffusion

Abstract: A number of enzymes reportedly exhibit enhanced diffusion in the presence of their substrates, with a Michaelis-Menten-like concentration dependence. Although no definite explanation of this phenomenon has emerged, a physical picture of enzyme self-propulsion using energy from the catalyzed reaction has been widely considered. Here, we present a kinematic and thermodynamic analysis of enzyme selfpropulsion that is independent of any specific propulsion mechanism. Using this theory, along with biophysical data … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Catalysis-fueled propulsion of biomolecules at the nanoscale is no doubt a fascinating concept and has potential applications in the field of nanoscience and medicine (42-49). However, mounting experimental and theoretical evidence argue against the mechanism, scale, and even the existence of such phenomenon (1,2,15,17,18,50). The vast majority of publications documenting enhanced enzyme diffusion upon catalysis were performed with FCS, which is prone to artifacts, such as free dye contamination, dissociation of enzyme quaternary structure and dye photophysics, that could result in apparent enhanced enzyme diffusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalysis-fueled propulsion of biomolecules at the nanoscale is no doubt a fascinating concept and has potential applications in the field of nanoscience and medicine (42-49). However, mounting experimental and theoretical evidence argue against the mechanism, scale, and even the existence of such phenomenon (1,2,15,17,18,50). The vast majority of publications documenting enhanced enzyme diffusion upon catalysis were performed with FCS, which is prone to artifacts, such as free dye contamination, dissociation of enzyme quaternary structure and dye photophysics, that could result in apparent enhanced enzyme diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Directly contradicting the FCS results by Illien et al, Zhang et al and Günther et al recently reported no diffusion enhancement of aldolase using dynamic light scattering (15) and pulsed field gradient nuclear magnetic resonance (16), respectively. On the other hand, theory suggests that the energy required to account for the experimentally observed diffusion enhancement far exceeds the chemical power released in enzymatic reactions (17). In addition, the change in the hydrodynamic radius of the enzyme needed to rationalize the observed diffusion enhancement is unlikely (18).…”
Section: Introductionmentioning
confidence: 99%